EVALUATING THE EFFECTIVENESS OF ANTIVIRUS EVASION TOOLS AGAINST WINDOWS PLATFORM (FUDMA JOURNAL OF SCIENCES, 2020)
Despite the prevalence of cyber-crimes, information and communication technology ICT has become the most convenient medium of communication and information exchanges. With this development, the information security breach is now one of the complex and challenging issues software developers are facing. The tools that have been developed for penetration testing with the purpose to raise the level of security strength, have been used also by malicious intruders to gain access to our devices. This paper aimed to evaluate the effectiveness of some selected antivirus (AV) evasion tools: Avet, Veil 3.0, PeCloak.py, Shellter, and a Fat Rat, against a Window platform. The selection of these tools was made for the purpose of testing how they can generate undetectable malware against the current best Antivirus Solution products in the market. This, in turn, revealed AV solutions with the best performance in detecting malware with evasion capability.  The paper adopted an experimental research design, in a Virtual lab setup with VMware Oracle VirtualBox, consisted of two machines (attacking and target machine). The results obtained indicated that the software evasion ranges from 0% to 83%. The Avet and PeCloak.py AV evasion tools were the best, while Kaspersky and Bitdefender antivirus appeared to be the best performing software protection in detecting the malware evasion tricks.
Keywords: Antivirus, Evasion Tools, Malware, Metasploit, Hackers